PENGEMBANGAN METODE PENENTUAN KARAKTERISTIK RANCANGAN AWAL ROTOR TURBIN ANGIN - Sulistyo Atmadi; Ahmad Jamaludin Fitroh (National Institute of Aeronautics and Space - LAPAN, 2007)
A method for determining design characteristics of a wind turbine rotor has been developed. Given the desired power and operational wind speed, the approximate design diameter and rotor rpm can then be determined. The size of the rotor diameter is governed by the blade performance, in which is normally given as power coefficient Cp; designed rotor spedd can be known after calculating the tip spedd ratio. Using this method, the blade and rotor characteristics can be designed quickly as a preliminary design parameter. Keywords: Rancangan awal, Koefisien daya, Tip speed ratio.